Constitutional Amendments in Indonesia: An Analytical Perspective of the Reformation Agenda - Mendy, Ousu (CV. Pustaka Parawali, 2025)
Constitutional amendments in Indonesia are commitments to end authoritarianism and usher in a democratic dispensation. This is one of the fundamentals of a new constitutional order. However, given the lack of political will, the four constitutional amendments have fallen short of the expectation of what they ought to have delivered. The study adopts a doctrinal legal scholarship through the exploration of opinions on constitutional amendments in relation to Pancasila democracy in Indonesia. This research seeks to establish that a fifth constitutional amendment is not necessary, as the previous amendments are not yet effectively implemented. The research finds that Indonesia’s democracy is in danger of regression because the current influence of anti-reformist elites depicts democratic stagnation and setbacks. As a civil law country, Indonesia has enacted an unprecedented number of pieces of legislation, and yet, it does not fulfil the dreams of the reformers. Indonesia lacks the political will to enforce norms that were created in the aftermath of the reformation agenda, and thus questions the essence of the four amendments. While new laws are a sine qua non of a new constitutional order, political will is a non-negotiable factor in implementation. This study, therefore, recommends that the State create an institutional transformation agenda for a new constitutional order in line with Pancasila. A fifth constitutional amendment is not necessary since the four amendments are yet to be fully implemented.